Seen and Imagined: A Northwestern Crossroads City (Imaginations: Journal of Cross-Cultural Image Studies, 2016)
Abstract | This paper is an interpretive study of Edmonton, Alberta that combines photography, written reflection, and analysis. Blending insider and outsider voices and perspectives, the essay represents the city through the imagery of a gritty, postmodern frontier. Edmonton is depicted as the locus of mixed and often contradictory energies, associated in significant ways with its northwestern character. The project developed through a process of photography and dialogue and is by nature suggestive and partial. It offers a visual-sociological engagement with a particular social environment and cultural landscape, whose look and feel are represented through a combination of photographic images and written text.Résumé | Cet article est une étude interprétative de la ville d’Edmonton qui combine photographie, réflexion écrite et analyse. En mêlant des points de vue externes et internes, cet essai représente la ville à travers l’imagerie d’une frontière postmoderne réaliste. Edmonton est peinte comme un lieu d’énergies diverses et souvent contradictoires, qui sont associées de manière significative avec son caractère du nord-ouest. Le projet s’est développé à travers un processus de photographie et de dialogue et, par nature, est subjective et partial. Il nous offre un engagement visuel sociologique avec un environnement social et un paysage culturel particulier, dont l’apparence et le ressenti sont représentés à travers un mélange d’images et de textes.